Pharmacokinetics and clinical evaluations of gentamicin-induced nephrotoxicity in puppies - Gberindyer, Fidelis A.; Omobowale, Temidayo O.; Abatan, Matthew O. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The study was aimed at investigating the effect of dosing intervals on gentamicin nephrotoxicity in puppies. Methods: Local puppies were assigned to Groups A and B (n=6) and administered gentamicin intramuscularly once (6 mg/kg) or twice (3 mg/kg) daily, respectively, for 5 consecutive days. Biochemical parameters such as urine protein, creatinine, ɤ-glutamyl transferase, as well as serum creatinine (SCR) and urea nitrogen were determined spectrophotometrically using specific kits before and after treatment. Peak and trough serum concentrations of gentamicin were determined by immunoassay on 1st and 5th day treatment. Thereafter, elimination rate constants and corresponding half-lives were calculated. Results: No significant increase in SCR concentrations in both groups was observed, but values on day 7 were slightly above normal. Conversely, there was a significant increase above normal in serum urea nitrogen on days 4 and 7 in Group A, whereas this was observed only on day 7 in Group B. Even though all other biochemical parameters assayed for were within normal, an increasing trend was noticed as the length of treatment days increased in both groups. In both groups, peak serum concentrations of gentamicin did not differ significantly. There was a 4- and 16-fold significant increase in trough levels after the last treatment in Groups A and B, respectively. Although peak and trough concentrations increased with increasing length of treatment, all the values were well below 10 µg/ml and 2 µg/ml, respectively, as required. Conclusion: These suggest the risk of nephrotoxicity following treatment with gentamicin beyond 5 consecutive days irrespective of the dosing interval in puppies.